Risk Factors Associated With the Development of Acquired Airway Disease After Congenital Heart Surgery: A Retrospective Cohort Study. (September 2018) - Matisoff, Andrew J.; Ari, Pranathi; Zurakowski, David; Espinel, Alexandra G.; Deutsch, Nina; Reilly, Brian K.
Objective . In this single-center, retrospective review, we sought to determine the risk factors associated with the development of severe acquired airway disease (AAD; vocal cord paralysis [VCP] or subglottic stenosis [SGS]) in pediatric patients who had undergone surgery for congenital heart disease (CHD) with cardiopulmonary bypass. All patients who required surgical treatment for CHD using cardiopulmonary bypass at our institution between 2010 and 2015 were reviewed. We defined severe AAD as either clinically significant VCP, SGS, or both, requiring consultation with the otolaryngology (ENT) service for evaluation. The disease was classified as severe because it led to difficulty with intubation or failure to wean mechanical ventilation. This airway disease was not present or was clinically insignificant prior to congenital heart surgery. Results . Over a 5-year period (August 2010 to December 2015), 1395 patients were evaluated. Of these, 25 (1.8%) had significant AAD. Age was the only statistically significant independent predictor of AAD ( P < .001). Those with AAD were younger—3 versus 8 months—and had longer intubation time: 5 (2-18) versus 2 days (1-5). Of those who developed AAD, most (22/25) required some form of additional surgical procedure for its evaluation or management. Only 3 of the 25 patients with severe AAD required tracheostomy. Conclusions . Children who undergo congenital heart surgery with cardiopulmonary bypass are at risk for developing AAD, most often because of SGS or VCP. AAD can lead to failed extubation in the postoperative setting as well as difficult intubation during subsequent anesthetics. Although it often requires surgical treatment, it responds well to therapy and rarely requires tracheostomy.